Preferred habitat and monetary policy through the looking-glass - Giacomo Carboni; Martin Ellison (European Central Bank (ECB), 2022)
The ability of monetary policy to influence the term structure of interest rates and the macroeconomy depends on the extent to which financial market participants prefer to hold bonds of different maturities. We microfound such preferred-habitat demand in a fully-specified dynamic stochastic general equilibrium model of the macroeconomy where the term structure is arbitrage-free. The source of preferred habitat demand is an insurance fund that issues annuities and adopts a liability-driven strategy to minimise the duration risk on its balance sheet. The optimising behaviour of the insurance fund implies a preferred- habitat demand function that is upward-sloping in bond prices and downward-sloping in bond yields, especially when interest rates are low. This supports the operation of a recruitment channel at low interest rates, whereby long-term interest rates react strongly to short-term policy rates because of complementary changes in term premia induced by preferred-habitat demand. The strong reaction extends to in‡ation and output in general equilibrium, a through-the-looking-glass result that challenges conventional wisdom that preferred habitat weakens the transmission of monetary policy.
Keywords: E43; E44; E52; G21; G22; 330; general equilibrium; interest rates; preferred habitat; term structure